LAPAROSCOPIC AND LAPAROSCOPIC-ASSISTED INTERVENTIONS IN THE SURGERY OF ACUTE ADHESIVE SMALL INTESTINAL OBSTRUCTION - Khujabaev S.T; Aslanov V.G; Dusiyarov M.M (Scholar Express Journals, 2025)
The results of complex diagnostics in 117 patients with OSTCN have been studied. The choice of the method of laparoscopic (64,3%) and laparoscopic-assisted (23,2%) surgical treatment of OSTCN in each case is strictly personalized and depends on the severity of adhesions, presence or absence of necrosis of the small intestine, character of exudate in the abdominal cavity, general condition of the patient according to the ASA scale and presence (more than 4 cm) or absence of total dilation of the small intestine loops; the presence of “acoustic window” for abdominal cavity puncture should also be taken into account. The application of differentiated surgical tactics with the use of the developed methods of surgical interventions, as well as cytokine, antioxidant, antihypoxant and serotonin therapy contributed to the decrease in the incidence of early postoperative intra-abdominal and wound complications by 12.0%, compared to the control group patients - 23.3%, also the number of distant postoperative complications decreased to 4.6% of cases, compared to the control group - 16.3%.
Keywords: Acute adhesive small intestinal obstruction; surgical treatment; laparoscopy